2020
DOI: 10.21037/apm-20-1293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of family integrated care on refractory cancer-related pain receiving intrathecal morphine pump therapy: a cohort study

Abstract: therapy recommended by the World Health Organization (WHO) helps improve the chronic pain in over 80% of cases (3). However, the therapy is still to do not relieve pain in 15-20% of cases due to drug tolerance or serious adverse events. To make up for the shortcomings of three-step analgesic ladder therapy, the novel, a fourth step, including several therapies, was put forward (4), of which intrathecal drug infusion was most discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Twenty-one studies were analyzed for the purpose of this review. Three were randomized controlled studies [6,7,20], nine were openlabel prospective studies [9,[20][21][22][25][26][27][28][29], and nine were retrospective studies [29][30][31][32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one studies were analyzed for the purpose of this review. Three were randomized controlled studies [6,7,20], nine were openlabel prospective studies [9,[20][21][22][25][26][27][28][29], and nine were retrospective studies [29][30][31][32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…In a prospective study, 33 patients were enrolled for implanting an intrathecal pump because of “refractory cancer-related pain” [ 29 ]. Authors showed that the implantation of intrathecal morphine pump relieved the pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another prospective study of 33 patients receiving morphine ITDD reported significant improvement in mean pain scores, Karnofsky performance scores (KPS), self-rating anxiety and depression scale scores at 1 year follow-up ( P < 0.001) [26]. No serious adverse events were observed in this study [26].…”
Section: Intrathecal Drug Deliverymentioning
confidence: 99%